A model-driven engineering platform for wireless sensor networks - Pruet Boonma (2018)
A wireless sensor network (WSN) is a complex system where a large number of computing devices (i.e., sensors) collect and exchange sensing data through noisy wireless communication channel. Traditionally, WSN applications are developed using programming languages such as C and java, this approach poses a steep learning curve for application developers, e.g. scientists and engineers, who might have limited knowledge of programming. This paper proposes a model-driven engineering (MDE) platform for WSN which is designed for application developers to rapidly implement and test a WSN application. It leverages the notion of feature modeling so that it allows developers to graphically and intuitively specify features (e.g., functionality and configuration policies) in their application. It also validate a set of constrains among features and finally generates runnable application code. For testing, it uses a formal method in order to estimate various properties of application code such as network lifetime. Evaluation results show that the estimator has acceptable accuracy while perform much faster than the simulator. © 2013 IEEE.